Once upon a time : a short history of fairy tale - Warner, Marina (Oxford University Press, 2014)
In ten succinct chapters, Marina Warner guides us through the rich world of fairy tale, from Cinderella and Hansel and Gretel to Snow White and Pan's Labyrinth. Exploring pervasive themes of folklore, myth, the supernatural, imagination, and fantasy, Warner highlights the impact of the genre on human understanding, history, and culture.